2022
DOI: 10.1111/asj.13721
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of miRNA–mRNA interactions in ovaries of aged mice

Abstract: Advanced maternal age and ovarian aging are deleterious to the quantity and quality of oocytes and epigenetic modifications, which can affect the health of offspring. However, relatively little is known about the regulation of microRNA‐mediated transcription during ovarian aging. We therefore aimed to identify age‐related mRNA and microRNA changes and their interactions in the ovaries of aged mice. We performed QuantSeq 3′mRNA and small RNA sequencing to compare their expression patterns in post‐ovulation ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…For example, miR-19b was highly enriched in the follicular fluid (FF), GCs of young cows and regulates genes associated with FoxO signaling, endocytosis, and NR3C1 in GCs [117]. Differentially expressed genes and miRNA interacted in young and senescent mice, which influenced folliculogenesis, oocyte growth and steroidogenesis [118]. It was shown that the expression of miR-23a and miR-27a was significantly higher in aged rats than in controls [119].…”
Section: Non-coding Rna and Pofmentioning
confidence: 99%
“…For example, miR-19b was highly enriched in the follicular fluid (FF), GCs of young cows and regulates genes associated with FoxO signaling, endocytosis, and NR3C1 in GCs [117]. Differentially expressed genes and miRNA interacted in young and senescent mice, which influenced folliculogenesis, oocyte growth and steroidogenesis [118]. It was shown that the expression of miR-23a and miR-27a was significantly higher in aged rats than in controls [119].…”
Section: Non-coding Rna and Pofmentioning
confidence: 99%
“…MiRNAs are small, endogenous, noncoding single-stranded RNA molecules with a length of approximately 22 to 24 nucleotides, which act as posttranscriptional regulators of gene expression [ 49 , 50 ]. Mature miRNAs can regulate gene expression through different mechanisms, including mRNA cleavage and translational inactivation [ 51 ].…”
Section: Introductionmentioning
confidence: 99%